2018
DOI: 10.1007/s10532-018-9830-4
|View full text |Cite
|
Sign up to set email alerts
|

Production, formulation and cost estimation of a commercial biosurfactant

Abstract: Due to their amphipathic nature, biosurfactants are multifunctional molecules that have considerable potential in several industries, especially the petroleum industry. In this study, the commercial production of a biosurfactant from Pseudomonas cepacia CCT6659 grown on industrial waste was investigated in a semi-industrial 50-L bioreactor for use in the removal of hydrocarbons from oily effluents. A concentration of 40.5 g/L was achieved in the scale up and the surface tension was reduced to 29 mN/m. The bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(17 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…Moreover, the authors concluded that yeast cultivation assisted with ultrasound led to an overall increase in the sophorolipids yield, attributing this result to cavitational effects that increase the cell permeability and improve WCO intake and metabolism of yeast cells. The production of biosurfactants by Pseudomonas cepacia from WCO was improved from 8 gÁL À1 (Silva et al, 2017) to 40.5 gÁL À1 (Silva et al, 2018), varying the scale from 500-mL Erlenmeyer flasks to a semi-industrial 50-L bioreactor. The biosurfactant yield obtained in Candida tropicalis cultures had an improvement of 40 %, 53 % and 75 % when produced in 2-L, 3-L and 50-L stirred tank bioreactors, respectively, comparatively to results attained in flasks experiments (Almeida et al, 2017;Junior et al, 2018).…”
Section: Biosurfactantsmentioning
confidence: 99%
“…Moreover, the authors concluded that yeast cultivation assisted with ultrasound led to an overall increase in the sophorolipids yield, attributing this result to cavitational effects that increase the cell permeability and improve WCO intake and metabolism of yeast cells. The production of biosurfactants by Pseudomonas cepacia from WCO was improved from 8 gÁL À1 (Silva et al, 2017) to 40.5 gÁL À1 (Silva et al, 2018), varying the scale from 500-mL Erlenmeyer flasks to a semi-industrial 50-L bioreactor. The biosurfactant yield obtained in Candida tropicalis cultures had an improvement of 40 %, 53 % and 75 % when produced in 2-L, 3-L and 50-L stirred tank bioreactors, respectively, comparatively to results attained in flasks experiments (Almeida et al, 2017;Junior et al, 2018).…”
Section: Biosurfactantsmentioning
confidence: 99%
“…Moreover, most commercial detergents/degreasing agents are petroleum based, many of which are nonbiodegradable and have a long half‐life in the environment (Rocha e Silva et al, 2019). Other important factors associated with these products are the high cost (ranging from R$ 28–51 per liter), inefficient grease removal, and corrosivity, which diminishes the useful life of parts and equipment in industrial plants (Almeida et al, 2016; Soares da Silva et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The main raw material used in soaps and hand sanitizers is petrochemicals based surfactant and ethanol (or isopropanol), respectively. Petrochemical based surfactants and ethanol are priced around US$ 1–3/kg and US$ 1.38/gallon, respectively ([ 51 ]; https://tradingeconomics.com/commodity/ethanol ). The major limitation of the commercialization of any bio-based product is the cost associated with its production and biosurfactants are not different.…”
Section: Economic Aspects Of Eco-friendly Soaps and Hand-sanitizersmentioning
confidence: 99%